Comparative Study between Sliding Mode Control and the Vectorial Control of a Brushless doubly fed induction generator - Oussama, Moussa; Rachid, Abdessemed; Said, Benaggoune; Benguesmia, Hani (جامعة الوادي - university of el oued, 2018)
Brushless doubly fed induction generators (BDFIG) show commercial promise for wind-power generation due to their lower capital and operational costs and higher reliability as compared with doubly fed induction generators. This paper proposes a robust sliding mode control of grid-connected brushless doubly fed induction generator (BDFIG). The developed algorithm is based on the decoupling control by using oriented grid flux vector control strategy. The decoupling of the active and the reactive stator powers insures an optimal performance of the BDFIG at the sub-synchronous region. The stator of this machine incorporates two sets of three phase windings with different number of poles, power winding (PW) and control winding (CW). The proposed method is tested with the Matlab/Simulink software. Simulation results illustrate the performances and the feasibility of the designed control
Article
Keywords: Brushless doubly fed induction generator (BDFIG), Vector control, Sliding mode control (SMC), Active and reactive power